Pengaruh Game Based Learning (GBL) Berbantuan Website Educaplay terhadap Literasi Digital dan Hasil Belajar Siswa Kelas VII SMP Negeri 2 Samarinda pada Materi Ekologi dan Keanekaragaman Hayati Indonesia - Wati, Puji Setia; Kurniawati, Zenia Lutfi; Masitah, Masitah; Maasawet, Elsje Theodora; Turista, Dora Dayu Rahma; Makkadafi, Suparno Putera (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Technology-based learning is crucial for 21st-century education to improve digital literacy and student learning outcomes. This study aims to determine the effect of Game Based Learning (GBL) assisted by educaplay on digital literacy and learning outcomes of seventh-grade students of SMP Negeri 2 Samarinda on the topic of Indonesian ecology and biodiversity. This study used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. This study involved 64 students as samples, divided into experimental and control classes. The research instruments included essay questions for cognitive learning outcomes and questionnaires for digital literacy. The results showed significant differences between the two groups. The average cognitive posttest of the experimental class (79.5) was substantially higher than that of the control class (68.8), with an N-gain value of 0.52 (moderate category). The increase in digital literacy in the experimental class was also significant, from an average of 107.5 to 145.69. The t-test confirmed the significance value (p<0.05). Thus, it can be concluded that Game-Based Learning (GBL) supported by educaplay is effective in improving students' cognitive learning outcomes and digital literacy skills.